Motivation in university students: life goals and learning attitudes - Moral Pajares, Encarnación; Pedrosa Ortega, Cristina; Gallego Valero, Leticia; Martínez Alcalá, Concepción; Barreda Tarrazona, Raquel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The methodological renewal promoted by the EHEA implies a new didactic approach, giving greater importance to motivational learning than to teaching. In this context, students’ life goals and their attitude towards learning are key determinants of their motivation. The aim of this work is to analyse the motivational and learning orientations of students in the Faculty of Social and Legal Sciences at the University of Jaén in order to propose actions, procedures, tactics and resources to the teaching staff that will have a favourable influence on student motivation, encourage participation and attendance in class and contribute to active learning.